(untitled) (Журналистика сериясы, 2016)
The entire universe is regardless of the global system. Information space, which is associated with the emerging advanced technologies in the world significantly increased many times. Great powers using their achievements are trying to influence and act. Of course, Kazakhstan , where abundant natural and human wealth cannot stay away from the change occurring at the global level. Our country joined to the gloabal process of media modernization as other developing counties of world. But day after day we are convinced that, in order to benefit from this process, we have to face diffeferent barriers which threaten our historical and cultural values.